Quantitative Analysis of Site-city Interaction Effects on Regional Seismic Damage of Buildings. Issue 8 (11th June 2022) - Tian, Yuan; Sun, Chujin; Lu, Xinzheng; Huang, Yuli
ABSTRACT: The regional seismic damage assessment methods based on time-history analysis usually ignore the site-city interactions (SCI). The SCI may influence the simulated seismic responses and damage states of buildings. However, very few studies have been conducted to quantify the SCI effects on the damage states of buildings. In this study, the SCI effects on the seismic damage of buildings were quantitatively analysed using an idealized building arrangement model and several real-world urban models. The results show that the SCI effects on the regional damage ratios are limited, especially for urban areas with various building types and irregular arrangements.